Adapting an evidence-based HIV behavioral intervention for South African couples - Wechsberg, W.M.; El-Bassel, N.; Carney, T.; Browne, F.A.; Myers-Franchi, Bronwyn; Zule, W.A. (BMC, 2015)
Background: In South Africa, heterosexual couples are at risk for HIV infection and transmission through substance use, gender-based violence and traditional gender roles, and sex risk behaviors such as having multiple partners and unsafe sex.